Legal Aspects Of Parents Who Forcibly Marry Children As Collateral For Debts And Receivables (Case Study In Timor-Leste) - Fatima De Jesus Martins, Natalino Jose; Subarkah, Ibnu; Alfaris, Muhammad Ramadhana (Academos, 2024)
Forced marriage to girls as collateral for debts and receivables carried out by parents in Timor-Leste is a major problem that is considered against human rights and legal norms in Timor-Leste. The practice of forced marriage not only violates human rights, but also contradicts various national and international legal regulations. The forced marriage is carried out by some parents in Timor-Leste because of several main factors and legal aspects of parents who have forcibly married their daughter's children as collateral for debts and receivables in Timor-Leste. This study discusses two main problems, namely First, what are the factors of forced marriage of girls as collateral for debts and receivables in Timor-Leste?; Second, what are the legal aspects of the act of forcibly marrying girls as collateral for debts and receivables in Timor- Leste? The method used in this study is a sociological juridical legal approach, empirical law research with a legal research approach that examines law which is conceptualized as actual behavior which involves interviews with related parties such as victims, families, and law enforcement. The results of this study conclude that: First, this forced marriage is carried out with several factors of parents who forcibly marry girls as collateral for debts and receivables. Second, the Legal Aspect that arises from the act of forcibly marrying girls as collateral for debts and receivables committed by parents in Timor-Leste.